The Magnetic Tracker with Improved Properties for the Helmet-Mounted Cueing System - Zhelamskij,Michail (2016)
ABSTRACT This article highlights both theoretical and experimental experiences in the field of helmet-mounted cueing systems. The current state of these systems is described as optical and hybrid. The adventures of the positioning under local magnetic field are considered, and the directions for further improvement of magnetic technology are identified. A new method is proposed for the local magnetic field creation to increase update rate, to reduce the influence of the Earth’s magnetic field, and to reduce energy consumption of helmet-mounted cueing systems in relation to known prototypes. A mathematical model of positioning field is offered. The accuracy of the field mathematical description is studied for different shapes of windings. The transients are investigated in the source of positioning field and in the interior of the cockpit. In addition, a mathematical model of magnetic measurements is proposed, and the main sources of measurement and positioning errors are investigated. The calculation algorithm of the helmet’s coordinates is considered based on the results of magnetic measurements. The results of physical models research are given, and the operation of a sample in the full range of angles is shown. The trial mapping is conducted for the field created by the source with a ferromagnetic core. Positioning of the helmet’s movement on specified paths is performed, and the results make it possible to figure out the next generation of helmetmounted cueing systems with extended angles range, higher angular and linear accuracy, increased update rate (200 Hz), and minimized influence of Earth’s magnetic field.